Evidence of a link between demographic rates and species habitat suitability from post release movements in a reinforced bird population. Issue 8 (22nd December 2014) - Monnet, Anne‐Christine; Hardouin, Loïc A.; Robert, Alexandre; Hingrat, Yves; Jiguet, Frédéric
<x xml:space="preserve">Abstract</x> Despite the increasing use of species distribution models for predicting current or future animal distribution, only a few studies have linked the gradient of habitat suitability (HS) to demographic parameters. While such approaches can improve the reliability of models, they can help to better predict the response of species to changes in HS over space and time, as induced by ongoing global change. Here, we tested whether the spatial variation in HS along the individual movement path is related to survival, using extensive tracking data collected from captive‐bred individuals translocated to reinforce the wild populations of houbara bustard. We first modelled and mapped the HS from presence data of wild individuals using niche models in a consensus framework. We further analysed survival of released individuals using capture–recapture modelling and its links to HS, as the trend in suitability from the release sites along movements. We found that the survival of released individuals was related to changes in HS along their movements. For instance, individuals which moved to sites of lower HS than their release sites have lower survival probabilities than the others, independently of the HS of the release sites and daily movement rate. Our results provide an empirical support of the relationship between HS and survival, a major fitness component.